Web-Based Furniture Sales Information System - Minah Jaya, Suhana (Jurnal Improsci, 2023)
The development of e-commerce in Indonesia can make something promising. Where the company is engaged in the production of furniture, wood processing production materials, multiplex and HPL finishing, with the goods produced ready for use by consumers. The goods produced are in the form of household furniture such as cupboards, tables, kitchen-sets, and other furniture items. The introduction method in marketing existing products at the company is by offering directly to consumers and also by participating in furniture and interior exhibitions held by certain activities. At this time, Teak Megah Furniture wants to expand the distribution of its sales area, namely by creating an online sales system or what can be called e-commerce. It is hoped that with this online sales system, company owners can reap more profits than usual. For this reason, the author created a system with the title in the final project "Web-Based Furniture Sales Information System